The Influence of E-Wom and Digital Marketing on Purchasing Decisions at Shopee Marketplace in Palembang City - Changreani, Evelyn; Manalu, Anggriani Boru; Purb, Rizki Fatricia; Putri, Destriana (Indonesian Journal Publisher, 2024)
The purpose of this study was to analyze the influence of Electronic Word of Mouth (E-WOM) and Digital Marketing on purchase decisions made by consumers on the Shopee marketplace, especially in Palembang City. The use of E-WOM and Digital Marketing has increased significantly with the development of social media and e-commerce. The research method used was a causality approach with quantitative data collected from 100 Shopee application users in Palembang City through an online questionnaire. The research results showed that E-WOM and Digital Marketing significantly influenced the purchasing decisions made on the Shopee marketplace. Every improvement in online reviews (E-WOM) regarding Shopee led to an increase in purchase decisions. Additionally, an effective Digital Marketing strategy also contributed positively to consumer purchase decisions. The use of technology and online media, particularly related to the Shopee marketplace, was recognized as an important factor in consumer behavior. This study helps to understand the importance of E-WOM and Digital Marketing in online marketing, with a focus on consumers in the city of Palembang. The practical implications of this study are that companies can improve their digital marketing strategies and manage online reviews effectively to positively influence consumer purchase decisions.